Aeolian Prokaryotic Communities of the Global Dust Belt Over the Red Sea - Aalismail, Nojood A.; Díaz-Rúa, Rubén; Ngugi, David K.; Cusack, Michael; Duarte, Carlos M. (Frontiers in Microbiology, 2020)
Aeolian prokaryotic communities (APC) are important components of bioaerosols transported free or attached to dust particles suspended in the atmosphere. Terrestrial and marine ecosystems are known to release and receive loads of prokaryotes into and from the surrounded atmospheric air. However, compared to terrestrial systems, there is a lack of microbial characterization of the atmospheric dust over the marine systems, such as the Red Sea, which receives significant terrestrial dust loads and is centrally located within the Global Dust Belt. Prokaryotic communities are likely to be particularly important in the Global Dust Belt, the area between west coast of North Africa and Central Asia supporting the highest dust fluxes in the planet. Here we characterize the diversity and richness of the aeolian prokaryotic community (APC) over the Red Sea ecosystem, the only sea fully contained in the Global Dust Belt. MiSeq sequencing targeting 16S ribosomal DNA of two hundred and forty aeolian dust samples collected at ~7.5-m high above the sea level at coastal and offshore sampling sites over a two-year period (2015-2017), revealed that the APC in the atmospheric dust are dominated by Proteobacteria (24.28%), Firmicutes (18.29%), Bacteroidetes (14.85%), and Actinobacteria (5.78%), which is transported from different sources and more diverse than prokaryotic communities of the Red Sea surface water with observations of high percentages of marine and soil prokaryotes in the air. Several groups of bacteria are more commonly present in the air than the Red Sea water samples, hence these groups may be traveled from other faraway sources during storms events and seasons in the Red Sea region, where APCs structure influenced by the concentration of aeolian dust particles.